Proposing Using Waist-to-Height Ratio as the Initial Metric for Body Fat Assessment Standards in the U.S. Army. (1st March 2017) - Bernstein, Stephen A.; Lo, Michael; Davis, W. Sumner
ABSTRACT: Objectives: Soldiers failing to meet Army Regulation 600-9 (AR 600-9) for weight-to-height standards are required to undergo body fat taping assessment. This article describes a clinical performance improvement project in which battalion medical staff identified a simpler way to improve on meeting AR 600-9 standards with proposing to use the waist-to-height ratio (WtHR) in place of the current methodology. Methods: During a yearlong combat deployment to Iraq from 2009 to 2010, 42 Soldiers (34 males, 8 females) were evaluated and monitored by battalion medical staff for weight and body fat loss. Mean body mass index and waist circumference were compared between baseline or initial assessment and final assessment. The percentage of Soldiers meeting body fat standards was compared among those who had attained a WtHR ≤ 55% versus those who had not. Results: By the final assessment, mean body mass index had decreased 2.21 kg/m 2 or 6.6% ( p = 0.002) and mean waist circumference had decreased 6.0 cm or 5.8% ( p = 0.008). All Soldiers who had attained a WtHR ≤ 55% met AR 600-9 body fat taping assessment standards and presented a professional military appearance. Conclusion: Attaining a WtHR ≤ 55% is an effective measure of body composition that was able to predict a Soldiers' achievement of body fat standards metric for meeting AR 600-9 standards and achieving a professional military appearance.